2016
DOI: 10.1111/jre.12384
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminus of amelogenin enhances osteogenic differentiation of human cementoblast lineage cells

Abstract: The C-terminus of amelogenin promotes the osteogenic differentiation of human cementoblast lineage cells, indicating the possible utility of C11 peptide in periodontal tissue regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…Amelogenins are crucial components of developing extracellular enamel matrix, which direct the organization and mineralization of enamel. Studies have demonstrated that C-terminus of amelogenins induces division, differentiation, and maturation of MSCs, especially in cementoblastic lineage cells (Kunimatsu et al, 2017(Kunimatsu et al, , 2018. Additionally, cementoblastic differentiation of mesenchymal progenitor cells is tightly maintained by an autocrine system mediated by parathyroid hormone (PTH)related peptide (PTHrP) and the PTH/PTHrP receptor, thereby preventing DMSCs from premature differentiation into cementoblasts (Takahashi et al, 2019).…”
Section: Cementogenesismentioning
confidence: 99%
“…Amelogenins are crucial components of developing extracellular enamel matrix, which direct the organization and mineralization of enamel. Studies have demonstrated that C-terminus of amelogenins induces division, differentiation, and maturation of MSCs, especially in cementoblastic lineage cells (Kunimatsu et al, 2017(Kunimatsu et al, , 2018. Additionally, cementoblastic differentiation of mesenchymal progenitor cells is tightly maintained by an autocrine system mediated by parathyroid hormone (PTH)related peptide (PTHrP) and the PTH/PTHrP receptor, thereby preventing DMSCs from premature differentiation into cementoblasts (Takahashi et al, 2019).…”
Section: Cementogenesismentioning
confidence: 99%
“…Previously, it was revealed that rh174, an amelogenin cleavage product lacking the N‐terminus (rh128), and the C‐terminal region of rh174 enhance the proliferation and mineralization of human cementoblast‐lineage cells compared with control groups. On the other hand, no obvious difference was observed in proliferation or mineralization following treatment with cleavage products lacking the C‐terminus (rh163) compared with control groups . In addition, a recent in vivo study demonstrated that EMD and a synthetic proline‐rich peptide promote wound healing compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, no obvious difference was observed in proliferation or mineralization following treatment with cleavage products lacking the Cterminus (rh163) compared with control groups. 22,46 In addition, a recent in vivo study demonstrated that EMD and a synthetic proline-rich peptide promote wound healing compared with the control. However, no significant wound repair differences were found in the Tyrosince-rich amelogenin peptide (TRAP) compared with the control in the oral mucosa in an incisional rat model.…”
Section: F I G U R E 4 Effects Of Lamp1 Blockade On the Enhancement Omentioning
confidence: 99%
“…It has been reported that a formerly identified peptide (STDKTTREEVD, C11), which is also derived from the C-tail of amelogenin, could promote the proliferation of mouse calvarial osteoblastic cells and the osteogenic differentiation of human cementoblast lineage cells by inducing expression of ALP, OCN and BSP [ 31 ]. In contrast, peptide derived from amelogenin lacking the C-terminus (rh163) had no significant effect on osteogenic differentiation of human cementoblast lineage cells as compared with untreated controls [ 23 ]. In a recent study, we found an antimicrobial peptide TVH-19, which contains a modified C-terminal sequence, could promote odontogenic differentiation of hDPCs in vitro and induce tertiary dentin formation in indirect pulp capping [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…We designed QP5, a 22-residue amelogenin-based peptide, which includes five tandem amelogenin (glutamine-proline-X sequence) repeats and a C-terminal ‘tail’ of amelogenin (TKREEVD). The C-terminal sequence of amelogenin has been reported to function in including differentiation of human cementoblast lineage cells [ 23 ]. In addition, peptide QP5 is capable of promoting initial remineralization of enamel caries in bovine and rat enamel [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%